Bioanalytical Method Development and Validation of Gemcitabine Hydrochloride by RP-HPLC Method - Rajesh, V.; Anupama, B.; Jagathi, V.; Varaprasad, K. (Asian Journal of Chemistry, 2011)
A simple, accurate, precise and sensitive HPLC method with UV detection was developed and validated to separate and detect gemcitabine hydrochloride in human plasma using capecitabine hydrochloride as an internal standard. Gemcitabine hydrochloride and capecitabine hydrochloride (internal standard) were extracted from human plasma using methanol protein precipitation and were chromatographed on a phenomenex C18 (250 mm × 4.6 mm. 5μm) column using 20 μL injection volume and detection at 270 nm. An isocratic mobile phase consisting of methanol: water (85:15 % v/v) was used to separate these drugs. The retention times of gemcitabine hydrochloride and internal standard were 4.6 and 6.2 respectively. The method was validated over the range of 406.10-4020.05 ng/mL. The limit of detection was 200 ng/mL and the limit of quantification was 400 ng/mL. Within and between-day precisions are less than 6.5 % for all quality control samples. The absolute recoveries of gemcitabine hydrochloride was greater than 90 % were achieved. The described method can be readily utilized for analysis of pharmaceutical products.